The severity of untreated caries in the deciduous and permanent teeth among children aged 6-12 years using PUFA and pufa index: a cross-sectional study - Suwargiani, Anne Agustina; Aripin, Dudi; Susilawati, Sri; Suryanti, Netty; Putri, Fidya Meditia; Yolanda, Yolanda; Maulidia, Ardena Hamdani; Mohd Yusof, Zamros Yuzadi (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The PUFA Index and pufa are used to measure the severity of dental and oral conditionwhich are not commonly used due to its novelty, and this index can be used to measure untreated dental caries7 and caries activity. The aims of study are to assess the severity of untreated caries in children’s deciduous and permanent teeth by using the PUFA and pufa index. Methods: An observational study using a cross-sectional study design was conducted among children who lived in Puteran village in Pager Ageung district, Tasikmalaya Regent, West Java, Indonesia. Purposive sampling was used, and the children who met the inclusion and exclusion criteria were invited to participate in the study. Severity of caries was assessed using the pufa and PUFA index for deciduous and permanent teeth, respectively. Severity of caries data were analysed using formulas for pufa and PUFA index. Results: A total of 206 children participated in the study. The PUFA assessment showed the severity of caries was high in the deciduous dentition with pufa index of 3.5 with SD 1,9-3,6 However, the PUFA assessment showed a relatively lower severity of caries in permanent teeth, with index PUFA of 0.5 with SD 1,9-3,6. The severity of caries was higher in the maxillary than the mandibular teeth in deciduous teeth. On the other hand, the severity of caries was higher in the mandibular than maxillary teeth in the permanent teeth. Conclusions: Each child aged 6 and 12 years in Puteran village had severe untreated caries in one permanent tooth and severe untreated caries in 3 to 4 of deciduous teeth. The findings of the study will be used to develop caries prevention and oral health promotion programs.KEYWORDS Caries, Severity, Deciduous, Permanent, teeth, PUFA, PUFA index, children